Feasibility of Simultaneous CT Colonography and Fully-Automated Bone Mineral Densitometry in a Single Examination - Summers, Ronald M. (2011)
PURPOSE: To show the feasibility of calculating the bone mineral density (BMD) from CT colonography (CTC) scans using fully-automated software. MATERIALS AND METHODS: Automated BMD measurement software was developed that measures the BMD of the first and second lumbar vertebrae on a CT scan and averages the two values to provide a per patient BMD estimate. The software was validated in a reference population of 17 consecutive women who underwent QCT and in a population of 475 women from a consecutive series of asymptomatic patients enrolled in a CTC screening trial conducted at three medical centers. RESULTS: The average (± st. dev) BMD was 133.6±34.6 mg/cc (95% CI [130.5, 136.7]) (n=475). In women aged 42–60 (n=316) and 61–79 (n=159), the average BMDs were 143.1±33.5 mg/cc and 114.7±28.3 mg/cc, respectively (p<0.0001). Fully automated BMD measurements were reproducible for a given patient with 95% limits of agreement of [−9.79, 8.46] mg/cc for the mean difference between paired assessments on supine and prone CTC. CONCLUSION: Osteoporosis screening can be performed simultaneously with screening for colorectal polyps.